STAT1 Is Essential for Antimicrobial Effector Function but Dispensable for Gamma Interferon Production during Toxoplasma gondii Infection - Gavrilescu, L. Cristina (American Society for Microbiology, 2004)
The opportunistic protozoan Toxoplasma gondii is a prototypic Th1-inducing pathogen inducing strong gamma interferon (IFN-γ) cytokine responses that are required to survive infection. Intracellular signaling intermediate STAT1 mediates many effects of IFN-γ and is implicated in activation of T-bet, a master regulator of Th1 differentiation. Here, we show that T. gondii-infected STAT1-null mice fail to upregulate the IFN-γ-dependent effector molecules inducible nitric oxide synthase (iNOS), IGTP, and LRG-47, which are required for mice to survive infection. Both T-bet and interleukin-12 receptor β2 (IL-12Rβ2) failed to undergo normal upregulation in response to T. gondii. Development of IFN-γ-producing CD4(+) and CD8(+) T lymphocytes was severely curtailed in the absence of STAT1, but a substantial level of STAT1-independent non-T-cell-derived IFN-γ was induced. Absence of STAT1 also resulted in increased IL-4, Arg1, Ym1, and Fizz1, markers of Th2 differentiation and alternative macrophage activation. Together, the results show that T. gondii induces STAT1-dependent T-lymphocyte and STAT1-independent non-T-cell IFN-γ production, but that effector functions of this type 1 cytokine cannot operate in the absence of STAT1, resulting in extreme susceptibility to acute infection.